2008
DOI: 10.1585/pfr.3.029
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-Periodic Growth of a Single Helical Instability in a Low-Aspect Ratio RFP

Abstract: Quasi-periodic growth of a single core-resonant instability has been observed in a low-aspect ratio (low-A) reversed field pinch experiment in RELAX. In round-topped current discharges, the innermost core resonant m = 1/n = 4 mode grows with suppression of the neighboring m = 1/n = 5, 6 modes. The resultant toroidal mode spectrum of the m = 1 modes is similar to that of the quasi-single helicity (QSH) state with higher amplitudes. These phenomena are discussed along with the low-A characteristic of RELAX, indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 7 publications
(9 reference statements)
2
11
0
Order By: Relevance
“…This dominant growth of the m = 1 / n = 4 component for a wide range of parameters and profiles agrees qualitatively with experimental observations in RELAX, in which QSH states of the 1/4 mode appear periodically with suppression of the other modes [8].…”
Section: Resultssupporting
confidence: 88%
“…This dominant growth of the m = 1 / n = 4 component for a wide range of parameters and profiles agrees qualitatively with experimental observations in RELAX, in which QSH states of the 1/4 mode appear periodically with suppression of the other modes [8].…”
Section: Resultssupporting
confidence: 88%
“…In the low-A RFP machine RELAX, a quasi-periodic transition to a QSH state in which the internally resonant single tearing mode grows significantly larger than other modes has been observed [4]. During the QSH state, the fluctuation power is concentrated in the single dominant m = 1 mode.…”
Section: Experimental Results and Comparison With Calculationsmentioning
confidence: 99%
“…This may allow easier access to the quasisingle helicity (QSH) state, in which the internally resonant single tearing mode grows significantly larger than other modes. In the low-A RFP machine RELAX [2,3], (R = 0.51 m, a = 0.25 m (A = 2)), a quasi-periodic transition to the QSH state has been observed [4]. During the QSH state, the fluctuation power is concentrated in the dominant single m = 1 mode.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, equilibrium analyses have shown that the innermost mode rational surface can be located away from the axis in a lower aspect ratio (A = R/a) of the RFP configuration, where R(a) is the major (minor) radius of the plasma Manuscript column. Therefore, the growth of a single mode to a higher amplitude can be expected in a low-A RFP than in medium-and high-A RFPs, which may allow easier access to quasi-singlehelicity (QSH) state, in which the internally resonant single tearing mode grows significantly larger than other modes.In a low-A RFP machine REversed field pinch of Low Aspect eXperiment (RELAX) [2] (R = 0.51 m/a = 0.25 m (A = 2)), a quasi-periodic transition to QSH state has been observed [3]. During the QSH state, the fluctuation power is concentrated to the dominant m = 1/n = 4 mode.…”
mentioning
confidence: 99%
“…In a low-A RFP machine REversed field pinch of Low Aspect eXperiment (RELAX) [2] (R = 0.51 m/a = 0.25 m (A = 2)), a quasi-periodic transition to QSH state has been observed [3]. During the QSH state, the fluctuation power is concentrated to the dominant m = 1/n = 4 mode.…”
mentioning
confidence: 99%